2016
DOI: 10.1534/g3.115.025841
|View full text |Cite
|
Sign up to set email alerts
|

Novel Heterotypic Rox Sites for Combinatorial Dre Recombination Strategies

Abstract: Site-specific recombinases (SSRs) such as Cre are widely used in gene targeting and genetic approaches for cell labeling and manipulation. They mediate DNA strand exchange between two DNA molecules at dedicated recognition sites. Precise understanding of the Cre recombination mechanism, including the role of individual base pairs in its loxP target site, guided the generation of mutant lox sites that specifically recombine with themselves but not with the wild type loxP. This has led to the development of a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
(93 reference statements)
1
15
0
Order By: Relevance
“…A number of Cre orthologues, including Dre and VCre, have recently been identified by genome mining and demonstrated to have in vivo function 23 25 . Additionally, Chuang et al 26 carried out an extensive mutant library screening, and identified novel rox sites, which can efficiently recombine with themselves in vivo but have minimal to no reactivity with wild-type (WT) rox sites 26 .…”
Section: Introductionmentioning
confidence: 99%
“…A number of Cre orthologues, including Dre and VCre, have recently been identified by genome mining and demonstrated to have in vivo function 23 25 . Additionally, Chuang et al 26 carried out an extensive mutant library screening, and identified novel rox sites, which can efficiently recombine with themselves in vivo but have minimal to no reactivity with wild-type (WT) rox sites 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, Dre does not crossreact with the Cre/LoxP system, but has similar recombination efficiency (Sauer and McDermott, 2004). The Dre/RoxP system has been previously tested in some settings (Chuang et al, 2015), but not yet widely used in gene targeting studies to generate lineage manipulation in animals.…”
Section: Introductionmentioning
confidence: 99%
“…To specifically target cells that express En1 in the adult, without interference from embryonic En1 domains, En1 Dre can be used in conjunction with injection of Dre‐responsive and Dre/Cre‐responsive viral constructs encoding indicators and effectors (Chuang et al ., ; Fenno et al ., ; Madisen et al ., ). Several of these recently described constructs utilize engineered mutant rox target sites to permit control of indicator or effector gene expression by Dre‐dependent inversion and excision similar to Cre‐dependent FLEx/DIO constructs (Chuang et al ., ; Fenno et al ., ). Given these possibilities, we expect that En1 Dre will become an important part of the genetic toolbox for analysis of neurons in the mammalian midbrain and hindbrain.…”
Section: Resultsmentioning
confidence: 98%
“…Thus, eGFP will be expressed in En1 Dre ; RC::RLTG brain only if Dre recombines the loxP sites as well as the rox sites. We observed no eGFP labeled cells ( n = 4 brains), consistent with prior observations that Dre and loxP sites are generally incompatible in transgenic systems (Chuang et al ., ; Park and Leach, ; Plummer et al ., ), with significant cross‐reactivity only observed in the context of viral vector‐driven overexpression (Fenno et al ., ). These results confirm that En1 Dre is suitable for use in intersectional genetic analyses together with Cre driver alleles.…”
Section: Resultsmentioning
confidence: 99%